Clinical Profile and Outcomes of Diabetic Ketoacidosis during the COVID-19 Pandemic in North India. (July 2022) - Kiran, Ravindran; Saroch, Atul; Pannu, Ashok Kumar; Sharma, Navneet; Dutta, Pinaki; Kumar, Mohan
Although recent data have shown a declining trend in mortality in diabetic ketoacidosis (DKA), the outcomes are likely to be different during the coronavirus (COVID-19) pandemic. We conducted a prospective cohort study to evaluate the spectrum and outcomes of adult DKA during the pandemic and document differences in DKA patients with or without COVID-19. A total of 169 patients (mean age 44 years) were admitted at the Emergency Department of PGIMER, Chandigarh (India), from January 2020 to June 2021. The precipitating factors were noncompliance with antidiabetic therapy (77.5%), infections (62.7%), and noninfectious conditions (21.3%). Thirty-nine (23.1%) patients had COVID-19, including 31 with severe infection. DKA severity and resolution, ventilator requirement, hospital stay, and mortality were similar in the patients with or without COVID-19. In-hospital mortality was 39.6% (n = 67). The independent mortality predictors were ventilator requirement ( p -0.000), an infection trigger ( p -0.049), and hyperosmolarity ( p -0.048). DKA mortality is increased significantly during the pandemic.